Effect on Lower Limb Motor Function of Cerebral Infarction Patients with Foot-drop Following Early Functional Electrical Stimulation - Hongyu LI; Luwen ZHU; Qiang TANG; Huijie CHEN (康复学报)
Objective:To investigate the effects on lower limb motor function of cerebral infarction patients with foot-drop following early functional electrical stimulation.Methods:Forty patients with foot-drop were randomly divided into control group and treatment group. Patients in both groups were given conventional rehabilitation after cerebral infarction. The treatment group was involved functional electrical stimulation on the basis of conventional rehabilitation. Before and after treatment, active ankle joint range of motion, lower limb motor function (Fugl-Meyer score) and walking ability (Step test time) were used to assess the improvement of patients with foot-drop.Results:After treatment, compared with control group, there were significantly improving in active ankle motion, lower limb motor function and walking ability in the treatment group (P<0.05).Conclusion:Early functional electrical stimulation can improve the active ankle joint degree of cerebral infarction patients with foot-drop, and improve lower limb motor function and walking ability.